Paracremastaptera, a new apterous genus of Mezirinae from China (Hemiptera: Aradidae) - Surnaa, Surnaa; Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2020)
A new apterous flat bug genus and species, Paracremastaptera ximaensis Bai, Heiss & Cai, gen. nov. and sp. nov., is described from Yunnan, China. The diagnostic morphological features of the new genus and species are illustrated.